Ni Una Más – Activist-Artistic Response to the Juárez Femicides - Benita Heiskanen (United Kingdom, 2022)
In the early 1990s, the cadavers of hundreds of women, many of whom were working in the maquiladora (border assembly plant) industry in the U.S.-Mexico border region,
started appearing mutilated, tortured, and often sexually abused in Ciudad Juárez,
Chihuahua, Mexico across the Río Bravo/Río Grande River from El Paso, Texas, U.S.A. These murders became known as ‘femicides’ or ‘feminicides’ (Spanish feminicidio). To date, nobody knows the exact number of the slain and disappeared women, as most of the murders remain uninvestigated and much of the original evidence has disappeared. The unwillingness to investigate the crimes has frustrated all parties involved, prompting the victims’ families and human rights groups to seek justice for the crimes through various grassroots measures.
The Juárez femicides also inspired a global activist-artistic movement to take a stand on the ways in which the victims were represented and commemorated in public
discourses. This article discusses one such endeavor, the activist-art exhibition ‘Ni Una Más, Not One More: The Juárez Murders’ that was featured in the Leonard Pearlstein Gallery at Drexel University in Philadelphia during May 15-July 16, 2010. The discussion draws from both the artwork – including photography, performance art, and installations – as well as interviews conducted with the artists from the United States, Mexico, and Europe. While the exhibition called attention to many of the issues that the nation-state, and its law enforcement agencies, had repeatedly failed to address, it also prompted a series of broader questions regarding visual/spatial contestations, individual vs. collective complicity, and the politicization of death.